1995
DOI: 10.1007/bf00299786
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy?Can conversion be predicted?

Abstract: The possibility of conversion to open cholecystectomy (OC) always exists while performing a laparoscopic cholecystectomy (LC). This study has been performed with the aim of identifying factors predicting conversion to OC. From October 1992-April 1994, LC was attempted in 150 patients and conversion to OC was required in 29 (19%) patients. Ten preoperative factors were analyzed retrospectively to identify parameters significantly correlating with conversion to OC. Preoperative factors analyzed were age, sex, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 10 publications
3
32
1
1
Order By: Relevance
“…12,13 In this study 68% had BMI≤30, and 32% patients were having BMI>30, but there was no significant difference in obese patients with regard to conversion rates and operative time (p>0.05).The reason for higher conversion rates in male patients remains unexplained, though male gender has been a significant risk factor in most series. 8,14 It has been observed that male patients have more intense inflammation or fibrosis, resulting in more difficult dissection both in the triangle of Calot's and through the plane between the GB and the liver. In our study we encountered difficulty in access in four patients.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In this study 68% had BMI≤30, and 32% patients were having BMI>30, but there was no significant difference in obese patients with regard to conversion rates and operative time (p>0.05).The reason for higher conversion rates in male patients remains unexplained, though male gender has been a significant risk factor in most series. 8,14 It has been observed that male patients have more intense inflammation or fibrosis, resulting in more difficult dissection both in the triangle of Calot's and through the plane between the GB and the liver. In our study we encountered difficulty in access in four patients.…”
Section: Discussionmentioning
confidence: 99%
“…Various conversion rates have been reported in the literature, ranging from 4.9% to 29%. [12][13][14] With limited number of patients, our conversion rates were 2.1% and 3%, in chronic and acute cholecystitis, respectively. Although there were high conversion rates in some studies, recent and large reports have shown marked decrease over time.…”
Section: Discussionmentioning
confidence: 77%
“…As expected, patients in the CONV group were older and more frequently male, which are reported risk factors for conversion. [15][16][17][18][19][22][23][24][25][26][27][28][29][30][31][32][33] The CONV group also had greater preoperative ASA scores and some comorbidities, such as hypertension (Table II). We corrected for these differences by using a multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%